Magic dark and strange - Powell, Kelly, 1991- (Margaret K. McElderry Books, 2020)
Catherine Daly's ability to awaken the dead for a final goodbye goes awry when she and Guy Nolan, the watchmaker's son, seek a watch but find, instead, a boy whose return from the dead draws danger to the three.